2011
DOI: 10.1111/j.1540-5907.2011.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Vote Buying and Social Desirability Bias: Experimental Evidence from Nicaragua

Abstract: Qualitative studies of vote buying find the practice to be common in many Latin American countries, but quantitative studies using surveys find little evidence of vote buying. Social desirability bias can account for this discrepancy. We employ a survey-based list experiment to minimize the problem. After the 2008 Nicaraguan municipal elections, we asked about vote-buying behavior by campaigns using a list experiment and the questions traditionally used by studies of vote buying on a nationally representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
200
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(228 citation statements)
references
References 34 publications
11
200
1
5
Order By: Relevance
“…This effect is considerable, but weaker than the impact of most of the other variables in the model. However, given the tendency of individuals immersed in clientelistic networks not to report it (Gonzalez-Ocantos et al, 2012), it is plausible that the effect is actually stronger than what the analysis reveals. Interestingly, the effect of vote buying is different in the long term.…”
Section: Resultsmentioning
confidence: 43%
“…This effect is considerable, but weaker than the impact of most of the other variables in the model. However, given the tendency of individuals immersed in clientelistic networks not to report it (Gonzalez-Ocantos et al, 2012), it is plausible that the effect is actually stronger than what the analysis reveals. Interestingly, the effect of vote buying is different in the long term.…”
Section: Resultsmentioning
confidence: 43%
“…List experiments offer one solution to this under-reporting problem by allowing respondents to communicate truthful information without openly admitting to illicit behaviors. In their study of vote-buying in Nicaragua, Gonzalez-Ocantos et al (2012) show that only 2% of respondents admitted they sold their vote when asked directly, whereas almost 25% did so when queried through the list experiment. We follow the same measurement strategy by using a list experiment on vote-selling.…”
Section: Vote-selling Turnout and Candidate Approvalmentioning
confidence: 99%
“…For example, Stokes (2005) and Stokes et al (2013) argue that vote-selling affects candidate approval, whereas Nichter (2008) argues that it increases turnout. Other work has shown that list experiments appear to improve the measurement of vote-selling behavior (Gonzalez-Ocantos et al 2012). Nevertheless, no existing method allows researchers to use this information about voteselling in a regression model to predict candidate approval and turnout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The list experiment (or item count technique) provides an appealing alternative to direct questioning and have recently attracted attention among social scientists (Blair and Imai, 2012;Glynn, 2013). For example, list experiments have been used to measure racial and gender discrimination (Kuklinski et al, 1997;Streb et al, 2008), voter turnout (Holbrook and Krosnick, 2010), clientelism (González-Ocantos et al, 2012) and support for militant groups and organizations (Blair et al, 2014).…”
Section: The List Experimentsmentioning
confidence: 99%